Molecular Approaches To Target GPCRs in Cancer Therapy - Innamorati, Giulio (MDPI, 2011)
Hundreds of G protein coupled receptor (GPCR) isotypes integrate and coordinate the function of individual cells mediating signaling between different organs in our bodies. As an aberration of the normal relationships that organize cells' coexistence, cancer has to deceive cell-cell communication in order to grow and spread. GPCRs play a critical role in this process. Despite the fact that GPCRs represent one of the most common drug targets, current medical practice includes only a few anticancer compounds directly acting on their signaling. Many approaches can be envisaged to target GPCRs involved in oncology. Beyond interfering with GPCRs signaling by using agonists or antagonists to prevent cell proliferation, favor apoptosis, induce maturation, prevent migration, etc., the high specificity of the interaction between the receptors and their ligands can be exploited to deliver toxins, antineoplastic drugs or isotopes to transformed cells. In this review we describe the strategies that are in use, or appear promising, to act directly on GPCRs in the fight against neoplastic transformation and tumor progression.